(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Alexander Arkadevich is very valuable to us, to the people of Uzbekistan, for his true patriotism of his homeland. The incomparable and unique work of Alexander Feinberg, infused with the best traditions of classical poetry and feelings of love for the land of Uzbekistan, is a special page in the history of our literature